Photodegradation of estrone in aqueous matrix, followed by HPLC - Groth, Milena Barbara (2015)
Endocrine disrupting chemicals (EDCs) are compounds with detrimental effects on the endocrine activity of the natural hormones in the human and animals. Besides industrial chemicals, some estrogens (both natural and synthetic) are found to be the most potent EDCs. Photodegradation is an important pathway for removing of estrogens from the aquatic system. Estrone (E1) is one of the steroidal estrogens existing widely in the aquatic environment and was found to be the most abundant estrogen in aquatic systems. The main goal of this work was to investigate the photodegradation of E1 in water under simulated solar radiation and to estimate the impact of different fractions of HSs (HA, FA and XAD-4). So far not many studies conducted on the impact of OM, existing in natural water on the photodegradation of E1. Therefore, the same experiment were done in the natural water with different content of OM, depending on the origin. The testing of E1 photodegradation with addition of singlet oxygen scavenger have been also performed. The results indicated that E1 was photodegraded even in the absence of OM with a half-life of 6 h. The presence of HSs enhanced the photodegradation in presence of all HS fractions accelerating the photodegradation of E1 with increasing concentrations of HSs. The effect of structural differences between HA, FA and XAD-4 on photodegradation of E1 has been studied. Experiments performed in natural water have shown the impact of origin of water samples on the rate of E1 photodegradation, which is related to different content of OM and salinity. The results of studies have shown inhibitory effect of the presence of sodium azide, as a singlet oxygen scavenger, on the photodegradation of E1. The presence of both OM and scavenger, have proven to reduce the photodegradation in both wastewater samples, but the effect was more pronounced in the case of sample after primary treatment (STPP). The LOD of 17.4 μg/L was achieved with HPLC-FLD procedure for the analysis of E1 in aqueous samples.